Dakwah Transformasional : Merespon Tren Sekulerisme Di Kalangan Gen Z - Muh Syahril Sidik Ibrahim Sidiq Ibrahim; Moch. Ainul Yaqin Ainul Yaqin; Zuhriyah Luluk Fikri Luluk Fikri (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
In the modern era, which is increasingly influenced by dominant secular culture, Generation Z faces significant challenges in maintaining and developing their spiritual and religious values. In this context, transformative preaching emerges as a promising approach to respond to this secular trend in a relevant and meaningful way. This research aims to explore the potential of transformative preaching in responding to the secular trend among Generation Z. We seek to understand how transformative preaching can assist Generation Z in finding meaning, depth, and spiritual direction in their lives, which are saturated with secular influences. The research methodology employed is qualitative, involving in-depth interviews and participatory observation with a sample group of Generation Z actively engaged in transformative preaching activities. Data analysis is conducted using an inductive approach to identify patterns and key findings. The main findings indicate that transformative preaching holds great potential in helping Generation Z overcome the challenges of secularism. The inclusive and open approach of transformative preaching creates a supportive environment for Generation Z to explore and deepen their understanding of spirituality. Additionally, the development of moral values and the utilization of social media and digital technology have proven effective in forming inclusive and supportive communities. This research makes a significant contribution to understanding the role of transformative preaching in responding to secular trends among Generation Z. These findings can aid in the development of more effective and relevant preaching programs to guide Generation Z in their search for meaning and spiritual direction in their complex lives.